2017
DOI: 10.4012/dmj.2016-124
|View full text |Cite
|
Sign up to set email alerts
|

Y-TZP zirconia regeneration firing: Microstructural and crystallographic changes after grinding

Abstract: This study evaluated microstructural and crystallographic phase changes after grinding (G) and regeneration firing/anneling (R) of Y-TZP ceramics. Thirty five bars (Lava TM and Ice Zirkon) were divided: Y-TZP pre-sintered, control (C), regeneration firing (R), dry grinding (DG), dry grinding+regeneration firing (DGR), wet grinding (WG) and wet grinding+regeneration firing (WGR). Grinding was conducted using a diamond bur and annealing at 1,000°C. The microstructure was analyzed by SEM and the crystalline phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
13
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 43 publications
5
13
1
6
Order By: Relevance
“…This property of zirconia provided satisfactory SBS values without showing phase transformation from t-m. However, other studies have reported phase transformation from t-m during grinding and sandblasting 31,32) . The conflicting results may be contributed to the different methodologies followed by the present and previous studies.…”
Section: Discussionmentioning
confidence: 89%
“…This property of zirconia provided satisfactory SBS values without showing phase transformation from t-m. However, other studies have reported phase transformation from t-m during grinding and sandblasting 31,32) . The conflicting results may be contributed to the different methodologies followed by the present and previous studies.…”
Section: Discussionmentioning
confidence: 89%
“…In general, it is known that temperatures above 1,000°C are sufficient for grazing of zirconia ceramics (850-950°C 18) ). This glazing also contributes to the re-crystallization of zirconia surface 19,20) . Thus, our hypothesis was that adjustment of the glazing (coating) material can improve the mechanical properties of PSZ through the re-crystallization process.…”
Section: Discussionmentioning
confidence: 99%
“…Alguns autores têm relatado que o desgaste pode causar transformação da fase tetragonal para fase monoclínica (Ho et al, 2009;Karakoca & Yilmaz, 2009;Maerten et al, 2013;Subasi et al, 2014;Gungor et al, 2015;Coldea et al, 2015;Lee et al, 2016;Ramos et al, 2016;Pereira et al, 2016A;Pereira et al, 2016B;Hatanaka et al, 2016;Ryan et al, 2017;Guilardi et al, 2017), enquanto outros não observam a presença desta fase após o desgaste (Kosmac, 2004;Denry & Holloway, 2006;Curtis et al, 2006;Amaral et al, 2013;Strasberg et al, 2014;Chun et al, 2017).…”
Section: Os Maiores Valores De Rugosidade Superficial Foram Obtidos Nunclassified
“…A presença de conteúdo cristalino na fase cúbica foi identificado por alguns autores quando a temperatura de sinterização foi de 1400°C a 1600°C (Scott, 1975;Ruiz & Readey, 1996;Matsui et al, 2003;Chevalier et al, 2004;Polli et al, 2016;Ryan et al, 2017) e após o desgaste (Curtis et al, 2006) devido ao estresse gerado durante este procedimento (Hasegawa et al, 1985). Entretanto, a presença desta fase não é muito relatada na literatura, porque pode haver sobreposição entre os planos da fase cúbica em relação a tetragonal, dificultando sua identificação (Denry & Holloway, 2006).…”
Section: Os Maiores Valores De Rugosidade Superficial Foram Obtidos Nunclassified
See 1 more Smart Citation